Pengaruh Current Ratio, Total Asset Turnover, dan Net Profit Margin terhadap Return on Assets - agus dwiatmoko (Universitas Nahdlatul Ulama Surabaya, 2026)
In general, most companies focus primarily on maximizing profits. They often overlook corporate obligations and fail to consider whether their assets are being effectively utilized for thecompany's benefit, even though these obligations and assets play a crucial role in achieving profitability. This study examines the factors influencing the return on assets of PT Nippon Indosari Corpindo Tbk, using the current ratio, total asset turnover, and net profit margin as independent variables. The objective of this research is to calculate and analyze the impact of the current ratio, total asset turnover, and net profit margin on the return on assets at PT Nippon Indosari Corpindo Tbk. Multiple regression analysis was employed as the data analysis method. The study utilized secondary data, specifically the financial statements of PT Nippon Indosari Corpindo Tbk—a company listed on the Indonesia Stock Exchange—covering the period from 2020 to 2025. These financial statements were subsequently analyzed using financial ratio analysis. The results indicate that the current ratio, total asset turnover, and net profit margin collectively (simultaneously) have a significant effect on the return on assets, with a significance value of 0.000. Individually (partially), the analysis reveals that the current ratio has a negative and insignificant effect on the return on assets (significance value of 0.892), whereas total asset turnover and net profit margin have a significant effect, with significance values of 0.008 and 0.002, respectively.